A Competence Development Approach for Entrepreneurial Mindset in Entrepreneurship Education. (7th July 2023) - Mawson, Suzanne; Casulli, Lucrezia; Simmons, Emilee L.
In recent years Entrepreneurship Education (EE) has become prevalent throughout Higher Education (HE), with a proliferation of programming for learners from Undergraduate to Post-experience studies. Despite the rapid scaling of provision, the majority of extant EE offerings demonstrate little conceptual evolution and development from early programs. Many approaches fall short of enabling the cognitive and behavioral change so critical to supporting entrepreneurial action. In this article we consider the concept of entrepreneurial mindset (EM) as a framing for EE programming, conceptualizing it as an approach to support the development of multidimensional cognitive and emotional competences and behavioral outcomes to enable entrepreneurial value creating activity across a range of contexts. We focus specifically on how educators can actively support the development of an EM through EE programming and start a conversation on the practicalities of operationalizing the EM concept within HE teaching and learning activity.